Interrater reliability of three-dimensional reconstruction of the spine: low-dose stereoradiography for evaluating bracing in adolescent idiopathic scoliosis - Al Mansour, Haidara; Pepke, Wojciech; Rehm, Johannes; Bruckner, Thomas; Spira, Daniel; Akbar, Michael (Der Orthopäde, 2020)
Bracing constitutes the mainstay treatment for mild scoliosis. The 3D reconstruction of the spine using low-dose stereoradiographic imaging (LSI) is increasingly being used to determine the true shape of the deformity and to assess the success of bracing.
Published online: 21 March 2019
Gesehen am 01.04.2020